(Retracted) Validation of Psychological Resilience Youth Developement Module and Implication for Guidance and Counseling - Suranata, Kadek Suranata; Atmoko, Adi; Hidayah, Nur (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
This study investigated the validation of the psychological resilience scale adaptation from youth development module (RYDM) for secondary school. The psychological RYDM is measured by six factors psychological assets was strongly associated with students academic success. A sample of study is 158 seventh grade students from five secondary schools in Singaraja, Bali Province (75 or 47.4% male and 83 or 52.6%  female, with age range 12-13 years). The constructs validation was conduct by exploratory factor analysis (EFA) method, with SPSS 22.0. Five iterations of the EFA reducing 18 original items to 14 items and 6 original factors to 5 factors. Five factors and 14 items produced are consistent with the conceptual basis used in the original RYDM. The stability of new five factors is formed by a split sample analysis method showed the all of the items of factors identified in the earlier testing stable adequacy of forming a common factor in this analysis in the first and second iteration. The results of analysis the item-total correlation on 14 item (n = 158) showed Cronbach's Alpha value of 0.777. Implications the study for guidance and counseling practice in schools is discussed.